IgG-RELATED DISEASE IN A PATIENT WITH PRIOR PANCREATIC CANCER AND SPLENOPANCREATECTOMY. (February 2015) - Orchard, Gregory R.; Arbelaez, Alejandro; Wong, David; Colosimo, Maree; Banh, Raymond H.
Abstract : IgG4-related disease is a newly recognised fibro-inflammatory condition characterised by a tendency to form tumefactive lesions in multiple sites; characteristic histopathological appearance with dense lymphoplasmacytic infiltrate, storiform fibrosis and obliterative phlebitis; and, often but not always, elevated serum IgG4 concentrations. We present a case of 69-year-old male with a past history of treated, recurrent mucinous carcinoma of the pancreas who presented with retroperitoneal, axillary and mediastinal lymphadenopathy and a renal mass. Axillary node excisional biopsy showed reactive changes with marked interfollicular increase in IgG4+ plasma cells, along with scattered non-necrotising granulomata. Core biopsies of the renal mass showed polymorphous infiltrate of lymphocytes and predominant plasma cells that stained IgG4. IgH and TCR gene rearrangements were polyclonal. Full blood count was normal other than eosinophilia. Serum IgG4 and IgE were significantly elevated at 11.70 g/L and 258 IU/mL respectively; CRP, ESR, IL-2 and IL-6 were normal. An infectious screen was also negative. The patient was diagnosed with IgG4-related disease and treated, with an excellent response, with prednisolone 0.6 mg/kg.